FACIES, ARCHITECTURE, AND ORIGIN OF A RESERVOIR-SCALE SAND-RICH SUCCESSION WITHIN SUBMARINE CONYON FILL: INSIGHTS FROM WAGON CAVES ROCK (PALEOCENE), SANTA LUCIA RANGE, CALIFORNIA, U.S.A - Anderson K.S.; Graham S.A.; Hubbard S.M. (My University, 2006)
Large submarine canyons incise most continental margins, but outcrops of comparably sized ancient examples are relatively rare. A preserved cross section of a filled Cretaceous-Paleocene submarine canyon, tens of kilometers wide by hundreds of meters deep and cut into granitic basement of the Salinian block, is exposed in the Santa Lucia Range of central coastal California. The exposure allows an opportunity for the detailed analysis of associated sand-rich deposits analogous to one type of petroleum reservoir. A succession of coarse-grained high-density turbidity current deposits present at Wagon Caves Rock (WCR), a 0.5 km2 mesa in the Indians Ranch area, is part of a lenticular sandstone body up to 75 in thick and several kilometers wide that accumulated within the confines of the submarine canyon. The facies architecture of the outcrop records canyon axial channel deposition in the middle reaches of the submarine canyon system. The uppermost beds at WCR record the catastrophic failure of the submarine-canyon wall, which was associated with the termination of coarse elastic deposition in the area. The modern Monterey submarine canyon, which incises Salinian block basement identical to that cut by the ancient canyon, provides a close analog for the depositional setting of the canyon deposits of the Indians Ranch area. The architectural analysis provides insight into facies and stratal architecture within a part of the deep-water slope environment that is relatively poorly known due to limited rock data from canyon successions and the inherent difficulty of recognizing large-scale submarine-canyon deposits in outcrop. Copyright © 2006, SEPM (Society for Sedimentary Geology).
Keywords: Cretaceous; Eocene; Paleocene; Mesozoic::Cretaceous; Мезозой::Меловая; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен; Cenozoic::Paleogene::Paleocene; Кайнозой::Палеоген::Палеоцен